When policy decisions for autism treatment in Europe are hijacked by a category mistake - Gillen, Eamonn; Keenan, Mickey (Psichologija, 2018)
Behavior analysts have an important role to play in the management of autism spectrum disorders (ASDs). While empirical support for interventions that are based on behavior analysis is extensive, this is not the case for many other kinds of interventions. This has resulted in significant differences in public policy and recommendations in different parts of the world, most notably between Europe and North America. In this paper, we outline some of the reasons for this disparity.